Occupational Profile and Perceptions of Street Children in Surat City - Patel, NB; Desai , Toral; Bansal, R K; Thakar, Girish (National Journal of Community Medicine, 2011)
Street children constitute a highly vulnerable, most deprived and marginalized section of the society, whose rights are constantly violated with impunity. This study attempts to explore the occupational profile of the street children in the city of Surat and pertinent aspects thereof. This cross-sectional study was conducted by interviewing 326 street children in Surat city. The study revealed that majority of the street children (79.8%) start earning money as beggars. They soon switch over to other petty jobs/ activities. The street children select their occupation according to their choice of work, availability of an opportunity and the amount of money available to them. Their occupational profile changes according to their age; the period of stay in Surat; and, the money available with them. The earnings of these children fluctuate with the season. Leading five occupations adopted by street children includes Working in eatables and tea stalls (11.7%); Begging and or sweeping (11.3%); Selling newspapers, magazines and books (11.3%); Shoe shining (9.8%) and Selling drinking water bottles & pouches & cold drinks (9.5%). Shoe shining is mostly carried out by the boys aged more than 12 years. Commercial sex work by girls is considered as inevitable by street girls. Illicit alcohol transport and selling is most lucrative and is often attract street children in to this occupation. Some street children become pick pockets under the guidance of an older pick pocket. Usually children who are very young, have recently come into the streets and their original families are often the most disadvantaged are more likely to engage in Picking up rags work as this requires no capital, no contacts and very less labour.